1994
DOI: 10.1111/j.1540-8159.1994.tb03829.x
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmias in Centenarians

Abstract: These data suggest that conduction disturbances of the AV nodal--His-Purkinje system and frequent SVPBs are common in centenarians, whereas very frequent VPBs and atrial fibrillation seem less common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…12 However, previous ECG studies in centenarians are limited by low sample size and methodological biases. 3,4,[12][13][14][15][16][17][18][19] The echocardiographic characteristics of centenarians have only been reported in a small retrospective group of 63 hospitalized subjects. 20 The aim of this study was to describe ECG, echocardiography, and blood test results in a cohort of centenarians and to correlate them with survival and with clinical data obtained from the medical history and a comprehensive geriatric assessment.…”
mentioning
confidence: 99%
“…12 However, previous ECG studies in centenarians are limited by low sample size and methodological biases. 3,4,[12][13][14][15][16][17][18][19] The echocardiographic characteristics of centenarians have only been reported in a small retrospective group of 63 hospitalized subjects. 20 The aim of this study was to describe ECG, echocardiography, and blood test results in a cohort of centenarians and to correlate them with survival and with clinical data obtained from the medical history and a comprehensive geriatric assessment.…”
mentioning
confidence: 99%
“…In one man 23,900 ventricular ectopic beats were detected; this rare occurrence was also previously reported in a study of younger participants that identified 1,100 ventricular ectopic beats in a woman [2]. In elderly men >1,000 ventricular ectopic beats in a 24-hour monitoring were identified in 4 (4.5%) individuals [3]. …”
Section: Discussionmentioning
confidence: 72%
“…between 50 and 83% [1, 2, 16, 33]; the increase relative to age was also observed by others, and reached in elderly subjects rates between 76 and 97.8% [3, 14, 16, 34]. In the patient with 3,694 atrial ectopic beats in spite of our strict criteria for inclusion in the study, a subclinical condition may not be ruled out.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations